The Role of Iron-Induced Fibrin in the Pathogenesis of Alzheimer’s Disease and the Protective Role of Magnesium - Pretorius, Etheresia; Lipinski, Boguslaw (Frontiers in Human Neuroscience, 2013)
Amyloid hypothesis of Alzheimer’s disease (AD) has recently been challenged by the increasing evidence for the role of vascular and hemostatic components that impair oxygen delivery to the brain. One such component is fibrin clots, which, when they become resistant to thrombolysis, can cause chronic inflammation. It is not known, however, why some cerebral thrombi are resistant to the fibrinolytic degradation, whereas fibrin clots formed at the site of vessel wall injuries are completely, although gradually, removed to ensure proper wound healing. This phenomenon can now be explained in terms of the iron-induced free radicals that generate fibrin-like polymers remarkably resistant to the proteolytic degradation. It should be noted that similar insoluble deposits are present in AD brains in the form of aggregates with Abeta peptides that are resistant to fibrinolytic degradation. In addition, iron-induced fibrin fibers can irreversibly trap red blood cells (RBCs) and in this way obstruct oxygen delivery to the brain and induce chronic hypoxia that may contribute to AD. The RBC-fibrin aggregates can be disaggregated by magnesium ions and can also be prevented by certain polyphenols that are known to have beneficial effects in AD. In conclusion, we argue that AD can be prevented by: 1) limiting the dietary supply of trivalent iron contained in red and processed meat; 2) increasing the intake of chlorophyll-derived magnesium; and 3) consumption of foods rich in polyphenolic substances and certain aliphatic and aromatic unsaturated compounds. These dietary components are present in the Mediterranean diet known to be associated with the lower incidence of AD and other degenerative diseases.